2002
DOI: 10.1002/1099-0682(200206)2002:6<1464::aid-ejic1464>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Copper(II) Complexes of Mono-, Bis-, and Tris(macrocyclic) Ligands and Inorganic or Organic Guests

Abstract: The copper(II)-assisted condensation of [Cu(2,3,2-tet)] 2+ [2,3,2-tet = bis-N,NЈ-(2-aminoethyl)propane-1,3-diamine] with formaldehyde and melamine (melamine = 2,4,6-triamino-1,3,5-triazine) afforded melamine-based mono-, bis-, and tris(macrocyclic) ligand/copper(II) complexes in approx. 30% overall yield. Three different monocopper(II), one dicopper(II), and one tricopper(II) complex structures are reported, as well as two structures of host-guest assemblies of the tricopper(II) complex with benzene-1,3,5-tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Thus the results obtained suggest that loss of water molecules of crystallization by the copper complex [Cu 3 L(H 2 O) 6 ](btc) 2 ·40H 2 O (I), which according to X-ray diffraction data [10] has a porous structure, is accompanied by certain changes in its crystal lattice. However, this does not lead to loss of porosity in the polycrystalline sample of this compound even after it is completely dehydrated down to [Cu 3 L](btc) 2 (III).…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Thus the results obtained suggest that loss of water molecules of crystallization by the copper complex [Cu 3 L(H 2 O) 6 ](btc) 2 ·40H 2 O (I), which according to X-ray diffraction data [10] has a porous structure, is accompanied by certain changes in its crystal lattice. However, this does not lead to loss of porosity in the polycrystalline sample of this compound even after it is completely dehydrated down to [Cu 3 L](btc) 2 (III).…”
mentioning
confidence: 83%
“…It has been shown that this compound has specific sorption properties [9]. Recently we described another complex with a similar crystal structure, [Cu 3 L(H 2 O) 6 ](btc) 2 ⋅40H 2 O (I), where L is a tris(macrocyclic) ligand constructed on the basis of melamine (2,4,6-triamino-1,3,5-triazine) [10]. …”
mentioning
confidence: 99%
See 3 more Smart Citations